Effects of 2, 3, 5-triiodobenzoic acid on the anatomical changes of chickpea var. BARI Chola-7 - Islam, Saiful; Rashid, Parveen (Dhaka University Journal of Biological Sciences, 2019)
Abstract not available Dhaka Univ. J. Biol. Sci. 28(2): 227-231, 2019 (July)